1992
DOI: 10.1557/jmr.1992.1870
|View full text |Cite
|
Sign up to set email alerts
|

Formation of mixed oxide powders in flames: Part II. SiO2−GeO2 and Al2O3−TiO2

Abstract: SiO2−GeO2 and Al2O3−TiO2 mixed oxide powders were synthesized using a counterflow diffusion flame burner. SiCl4, GeCl4, Al(CH3)3, and TiCl4 were used as source materials for the formation of oxide particles in hydrogen-oxygen flames. In situ particle sizes were determined using dynamic light-scattering. Powders were collected using two different methods, a thermophoretic method (particles are collected onto carbon coated TEM grids) and an electrophoretic method (particles are collected onto stainless steel str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 11 publications
1
19
0
1
Order By: Relevance
“…He concluded that oxygen vacancies promoted crystallite growth and the anatase to rutile transformation. Hung et al [12] obtained a mixture of TiO 2 , Al 2 O 3 and aluminum titanate on a microscopic scale when they synthesized TiO 2 -Al 2 O 3 composite particles in a counter flow diffusion flame. Powell et al [13] prepared titania particles from the oxidation of titanium tetrachloride in a hot-wall, tubular, aerosol reactor and directly coated by SiO 2 in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…He concluded that oxygen vacancies promoted crystallite growth and the anatase to rutile transformation. Hung et al [12] obtained a mixture of TiO 2 , Al 2 O 3 and aluminum titanate on a microscopic scale when they synthesized TiO 2 -Al 2 O 3 composite particles in a counter flow diffusion flame. Powell et al [13] prepared titania particles from the oxidation of titanium tetrachloride in a hot-wall, tubular, aerosol reactor and directly coated by SiO 2 in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts by Hung and Katz to produce mixed oxide powders nanoparticles of the core/shell type by flame synthesis. [10,11] lead to coated clusters, too. Entirely different is the approach of Jiao et al applying a modified Krätschmer-method to coat Fe, Co and Ni nanopar-REVIEWS ticles with amorphous carbon or graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of silica-coated particles by wet chemical process can be found, for example, in the literature. [8,9] Hung et al [10] report on the formation of mixed oxide powders consisting of silica, alumina, germania, and titania using a counterflow diffusion flame burner. Hartmann et al [11] present the production of highly dispersed ZrO 2 -, Al 2 O 3 ±TiO 2 -, and SiO 2 -doped powders by high-temperature hydrolysis of gaseous metal chlorides.…”
Section: Introductionmentioning
confidence: 99%